2011
DOI: 10.1186/1756-3305-4-112
|View full text |Cite
|
Sign up to set email alerts
|

Toxoplasma gondii infection and abdominal hernia: evidence of a new association

Abstract: BackgroundWe performed a retrospective, observational study in 1156 adult subjects from the general population of Durango City, Mexico, Fifty five subjects with a history of abdominal hernia repair and 1101 subjects without hernia were examined with enzyme-linked immunoassays for the presence of anti-Toxoplasma IgG and IgM antibodies.ResultsThe seroprevalence of anti-Toxoplasma IgG antibodies and IgG titers was significantly higher in subjects with abdominal hernia repair than those without hernia. There was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
(22 reference statements)
1
14
0
Order By: Relevance
“…is focused predominantly in reaching the main aim rather than secondary aims. Secondly, in the present study, we studied 391 cases, whereas the number of cases was low in previous studies, i.e., 55 cases were analyzed in the study of hernia repair [16], 95 in women with a history of stillbirths [11], 23 in Yoremes [17], and 193 in people applying for medical certificates [12]. Thirdly, the research method used in the present study is more stringent for assessing an association that those used in previous studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…is focused predominantly in reaching the main aim rather than secondary aims. Secondly, in the present study, we studied 391 cases, whereas the number of cases was low in previous studies, i.e., 55 cases were analyzed in the study of hernia repair [16], 95 in women with a history of stillbirths [11], 23 in Yoremes [17], and 193 in people applying for medical certificates [12]. Thirdly, the research method used in the present study is more stringent for assessing an association that those used in previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…In Durango City, we found a positive association between T. gondii infection and a history of surgery in psychiatric patients [10], women with a history of stillbirths [11], and people applying for medical certificates [12]. Similarly, T. gondii infection was associated with a history of hernia repair [16]. In addition, in a study of Yoremes, an ethnic group in the northwestern Mexican State of Sonora, we found that T. gondii exposure was associated with a history of cesarean sections in the women surveyed [17].…”
Section: Resultsmentioning
confidence: 99%
“…However, none of the women in our study had undergone surgery for transplantation. In a previous study, history of abdominal hernia repair was linked to T. gondii seropositivity, although it was not clear whether this link was due to the surgery or by muscle damage by T. gondii [ 22 ]. However, none of the women in our study had a history of abdominal hernia repair.…”
Section: Discussionmentioning
confidence: 99%
“…However, seropositivity in patients was associated with consumption of deer, quail and lamb meat 26 . In a retrospective study, a significant association between the presence of IgG antibodies and an age ≥ 50 years was reported 8 .…”
Section: Human Studies In Mexicomentioning
confidence: 99%